(untitled) (Ex Chordis, 2024)
Ottorino Respighi. A symphonic iceberg by Francesco Attardi and Lorenzo Casati is a wide-ranging, valuable monograph recently published by LIM that aims to bring to light the great, submerged symphonic heritage of Ottorino Respighi (Bologna, 1879 - Rome, 1936), too often neglected by sector critics, seeking to reveal the composer’s many human and artistic aspects in order to rediscover, and re-evaluate the face of the symphonist Respighi, author not only of the very famous triptych Fountains, Festivals and Pines of Rome, but also of over forty compositions for orchestra, and for soloist and orchestra, of a high standard, carefully presented in the Appendix in the catalogue edited by Floriana Pedarra - founder of the Centre for Respighi Studies in Milan - on the guidance of the musicological research carried out by her father, Potito Pedarra.